Body mass index and outcomes in ischaemic versus non-ischaemic heart failure across the spectrum of ejection fraction. (2nd June 2020) - Gentile, Francesco; Sciarrone, Paolo; Zamora, Elisabet; De Antonio, Marta; Santiago, Evelyn; Domingo, Mar; Aimo, Alberto; Giannoni, Alberto; Passino, Claudio; Codina, Pau; Bayes-Genis, Antoni; Lupon, Josep; et al.
Abstract: Aims: Obesity is related to better prognosis in heart failure with either reduced (HFrEF; left ventricular ejection fraction (LVEF) < 40%) or preserved LVEF (HFpEF; LVEF ≥50%). Whether the obesity paradox exists in patients with heart failure and mid-range LVEF (HFmrEF; LVEF 40–49%) and whether it is independent of heart failure aetiology is unknown. Therefore, we aimed to test the prognostic value of body mass index (BMI) in ischaemic and non-ischaemic heart failure patients across the whole spectrum of LVEF. Methods: Consecutive ambulatory heart failure patients were enrolled in two tertiary centres in Italy and Spain and classified as HFrEF, HFmrEF or HFpEF, of either ischaemic or non-ischaemic aetiology. Patients were stratified into underweight (BMI < 18.5 kg/m 2 ), normal-weight (BMI 18.5–24.9 kg/m 2 ), overweight (BMI 25–29.9 kg/m 2 ), mild-obese (BMI 30–34.9 kg/m 2 ), moderate-obese (BMI 35–39.9 kg/m 2 ) and severe-obese (BMI ≥40 kg/m 2 ) and followed up for the end-point of five-year all-cause mortality. Results: We enrolled 5155 patients (age 70 years (60–77); 71% males; LVEF 35% (27–45); 63% HFrEF, 18% HFmrEF, 19% HFpEF). At multivariable analysis, mild obesity was independently associated with a lower risk of all-cause mortality in HFrEF (hazard ratio, 0.78 (95% confidence interval (CI) 0.64–0.95), p = 0.020), HFmrEF (hazard ratio 0.63 (95% CI 0.41–0.96), p = 0.029), and HFpEF (hazard ratio 0.60 (95% CI 0.42–0.88), p = 0.008). Both overweight and mild-to-moderate obesity were associated with better outcome in non-ischaemic heart failure, but not in ischaemic heart failure. Conclusions: Mild obesity is independently associated with better survival in heart failure across the whole spectrum of LVEF. Prognostic benefit of obesity is maintained only in non-ischaemic heart failure.